Using Myofascial Therapy to Improve Psychological Outcomes, Quality of Life, and Sexual Function in Women with Chronic Pelvic Pain-A Case Series. - Díaz-Mohedo, Esther; Hita-Contreras, Fidel; Castro-Martín, Eduardo; Pilat, Andrzej; Pérez Domínguez, Borja; Valenza-Pena, Geraldine (MDPI, 2024)
Background: Chronic pelvic pain represents a prevalent condition afflicting women. Research has highlighted the presence of psychological distress and sexual dysfunction in these individuals. Regrettably, myofascial pelvic pain often goes unnoticed and untreated despite its integral role in chronic pelvic pain. (2) Methods: By employing a longitudinal case series design, we studied eighteen women afflicted with chronic pelvic pain. Over a 12-week period, these participants underwent 15 sessions of myofascial therapy. Data encompassing sociodemographic particulars, the Hospital Anxiety and Depression Scale, the Medical Outcomes Study Short Form 12 questionnaire, and the Female Sexual Function Index were collected at baseline, 12 weeks post-intervention, and again at the 24-week mark. (3) Results: After a span of 12 weeks subsequent to the intervention, the participants demonstrated noteworthy enhancements (p < 0.001) in their depression and anxiety scores, their overall Mental Component scores in the Medical Outcomes Study Short Form 12, as well as sexual function. Importantly, these gains were sustained at the 24-week juncture post-therapy. (4) Conclusions: The findings stemming from our prospective case study underscore the potential utility of myofascial therapy for women grappling with chronic pelvic pain. This form of intervention yields significant advancements in alleviating anxiety, depression, health-related quality of life, and sexual function.
Keywords: Dolor - Aspectos psicológicos; Dolor pélvico - Fisioterapia; Dolor miofascial - Fisioterapia; myofascial pain syndromes; pelvic pain; sexual dysfunction